TENDENCIES AND FORMS ОF SOCIAL TRANSFORMATIONS - T.A. BONDARENKO (Advanced Engineering Research)
The article of reconstructs the mechanism of between Virtual reality and social space of modern society, reveals the main tendencies and forms of social transformations as the  result of this interaction. Actual and future changes in social structure and social relations are also marked out in the article.